Russia and peak-oil demand. Issue 6 (3rd July 2021) - Unknown
Abstract : Russia relies on oil income to fund its government budget and to manage its macroeconomic affairs. The decline of crude-oil prices in 2014–16 and in 2020 - the first due to oversupply and the second to a pandemic-related drop in demand - was a painful reminder of this fact. It was also a preview of the moment in the future when global demand for oil will begin to permanently decline. It is unclear when this will occur, but when it does, it could threaten the political economy of the Russian government in a more comprehensive way than any prior economic or political challenge in recent memory.